Evaluation of L-carnitine's protective properties against AlCl3-induced brain, liver, and renal toxicity in rats. - Haifa Ali Alqhtani (PLoS ONE)
A common heavy metal in many facets of daily life is aluminum (AlCl3), which can be found in food, toothpaste, cosmetics, food additives, and numerous pharmaceutical items. The hippocampus, liver, and kidneys have the highest concentrations of this powerful neurotoxin, which also accumulates over time and contributes to the development of a number of cognitive disorders. Long-term overconsumption of AlCl3 results in hepatic and renal toxicity as well as neuronal inflammation. The purpose of the research is to assess the potential protective effects of various L-carnitine dosages as an antioxidant against hebato, renal, and neuronal toxicity in rats caused by aluminum chloride (AlCl3) (20 mg/kg, 1/20 LD 50). Six groups (n = 6), consisting of 36 adult albino rats, were randomly assigned. Saline was administered to the control group (GI) by injection. (GII) had given an injection of L-carnitine at a low-dose of 75 mg/kg body weight. An injections of L-carnitine at a high-dose (150 mg/kg) were given to (GIII), and AlCl3 (20 mg/kg) was given to (GIV). (GV) administered with L-carnitine (75 mg/kg) and AlCl3 (20 mg/kg) by injection. For 60 days, AlCl3 (20 mg/kg) and L-carnitine (150 mg/kg) were administered to GVI by injection. Furthermore, the histological structure of the cortex, hippocampus, and hepatic renal tissues appeared to change in response to AlCl3. L-carnitine therapy lessened the negative effects of AlCl3. The observable improvement in the tissues of the brain, liver, and kidneys further supported this histopathologically. It is possible to draw the conclusion that L-carnitine holds promise as a corrective measure for AlCl3, which causes renal toxicity and neural hepatotoxicity in rats. When it comes to adult albino rats, L-carnitine has a negative impact and exhibits ameliorative effects against aluminum chloride.